Effects of ferric iron on the anaerobic treatment and microbial biodiversity in a coupled microbial electrolysis cell (MEC) – Anaerobic reactor - Zhang, Jingxin; Zhang, Yaobin; Quan, Xie; Chen, Shuo (Water research (Oxford), 2013)
Adding Fe(III) into a MEC – anaerobic reactor enhanced the degradation of organic matters. To clarify the respective effects of combining Fe(III) dosage and a MEC and Fe(III) dosage only on strengthening anaerobic digestion, three anaerobic reactors were operated in parallel: a MEC – anaerobic reactor with dosing Fe(OH)3 (R1), an anaerobic reactor with dosing Fe(OH)3 (R2) and a common anaerobic reactor (R3). With increasing influent COD from 1500 to 4000 mg/L, the COD removal in R1 was maintained at 88.3% under a voltage of 0.8 V, which was higher than that in reactor R2 and R3. When the power was cut off, the COD removal in R1 decreased by 5.9%. The addition of Fe(OH)3 enhanced both anaerobic digestion and anodic oxidation, resulting in the effective mineralization of volatile fatty acids (VFAs). The reduced Fe(II) combined with electric field resulted more extracellular polymeric substances (EPS) production. Quantitative real – time PCR showed a higher abundance of bacteria in the anodic biofilm and R1. Pyrosequencing and denaturing gradient gel electrophoresis (DGGE) analysis revealed that the dominant bacteria and archaea communities were richer and more abundant in the anode biofilm and R1. [Display omitted] •Fe(III) dosing enhanced anaerobic digestion.•Combining a MEC and Fe(III) enhanced anaerobic digestion of organics with respect to Fe(III) only.•The reduced Fe(II) combined electric field helped to improve EPS production.•Increased EPS and Fe(II) were favorable for the enrichment of bacteria in anode biofilm and R1.•Fe(III) dosing helped to enrich more bacterial and archaeal communities in R1.